2022
DOI: 10.3390/ph15080911
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Current and New Therapies for Hemophilia A

Abstract: Anti-drug antibody (ADA) development is a significant complication in the treatment of several conditions. For decades, the mainstay of hemophilia A treatment was the replacement of deficient coagulation factor VIII (FVIII) to restore hemostasis, control, and prevent bleeding events. Recently, new products have emerged for hemophilia A replacement therapy, including bioengineered FVIII molecules with enhanced pharmacokinetic profiles: the extended half-life (EHL) recombinant FVIII products. However, the main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…After our stringent data sanitation, our dataset contained 626 HA cases (293 mild, 123 moderate and 210 severe), as well as the position and the amino acid substitution of each patient ( Figure 2A ). While patients with severe HA require prophylactic care that consists of intravenous injections 2-3 times per week, treatment for mild and moderate cases often require intravenous injections only when an injury occurs ( Prezotti et al, 2022 ). For this reason, we grouped the mild/moderate cases into one class and severe into another (majority class ratio of 0.66).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After our stringent data sanitation, our dataset contained 626 HA cases (293 mild, 123 moderate and 210 severe), as well as the position and the amino acid substitution of each patient ( Figure 2A ). While patients with severe HA require prophylactic care that consists of intravenous injections 2-3 times per week, treatment for mild and moderate cases often require intravenous injections only when an injury occurs ( Prezotti et al, 2022 ). For this reason, we grouped the mild/moderate cases into one class and severe into another (majority class ratio of 0.66).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, aiming at creating recombinant FVIII proteins with improved half-life, immunogenic and folding profiles ( Prezotti et al, 2022 ), we retrained these models to predict the coagulation activity of more than 300 alanine mutations. As a result, we found that the GNN models reliably predict the reduction in the activity of FVIII, effectively emulating in silico the results of costly and laborious in vitro assays.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has the potential to be applied in combination as a pretreatment to a number of immunogenic biologics in which ADA responses can limit therapeutic efficacy. Examples of potential use cases include preventing ADAs to chronically administered monoclonal antibody therapies such as adalimumab 62 , enzyme replacement therapies such as phenylalanine ammonia lyase for the treatment of phenylketonuria 63 and factor VIII replacement for hemophilia A 64 .…”
Section: Discussionmentioning
confidence: 99%
“…61 Potential differences in the immunologic mechanisms underlying inhibitor development in severe and NSH A may help explain possible differences in response to different factor replacement products. 62 Conflicting data from patients with severe hemophilia A suggested a difference in risk of inhibitor development with different therapeutic concentrates, but casecontrol data from the INSIGHTstudy (75 patients with inhibitors and 223 controls) have shown no increased risk of inhibitors in patients with nonsevere disease for any type of FVIII product. 63 For PWNSH affected by inhibitors, the approach to immune tolerance induction is advocated on a case-by-case basis 64 and the importance of close follow-up has been stressed.…”
Section: Inhibitorsmentioning
confidence: 99%